Low HCMV DNA Copies Can Establish Infection and Result in Significant Symptoms in Extremely Preterm Infants: A Prospective Study - Wakabayashi, Hitomi; Mizuno, Katsumi; Kohda, Chikara; Negoro, Takaharu; Maekawa, Chiaki; Sawato, Satomi; Tanaka, Kazuo; Nakano, Yasuko; Murayama, Junichirou; Taki, Motohiro; Miyazawa, Tokuo; Murase, Masahiko; Aizawa, Madoka; Nakano, Yuuya; Sakurai, Motoichiro; Takahashi, Kenichiro; Itabashi, Kazuo (American Journal of Perinatology, 2012)
Breast milk (BM) is the main source of human cytomegalovirus (HCMV) infection. We examined whether the number of HCMV DNA copies in BM is related to HCMV infection in very low birth weight (VLBW) infants. We identified 11 pairs of VLBW infants and mothers. BM samples were collected every week until 10 weeks postpartum. Urine samples were collected from the infants within 1 week, at 6 to 8 weeks, at discharge, and whenever HCMV infection was suspected. HCMV DNA in BM was positive in 7 of 11 mothers and reached a peak at 4 to 5 weeks postpartum. Of the 11, 5 infants were determined to be infected from positive HCMV DNA in the urine, despite the fact that BM was used after being frozen. Of the five, four infected infants exhibited symptoms between 35 and 60 days of age. Symptomatic infants had longer stays and slower weight gain. The HCMV infection rate is high in very preterm infants. A new strategy to prevent HCMV infection other than freezing should therefore be established.
Keywords: extremely preterm infants; cholestasis; pneumonitis